1957
DOI: 10.1177/004051755702700301
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Dyeing Polyester and Polyacrylic Fibers1

Abstract: These two fiber classes are similar in that both are dyed by disperse-type dyes; however, polyacrylic fibers can be dyed with anionic dyes if positive sites are provided. This can be done, for example, by using fiber containing ammonium groups. Alterna tively, positive sites in the form of bound cuprous ions can be produced by treatment of the fiber with cuprous salts. In either case, ion exchange occurs in which colorless anions and dye amons compete for positive sites in the fiber. In contrast, disperse dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…From the perspective of the disperse dye/PET fibre system, in 1954, Schuler and Remington 18 observed that rectilinear, Nernst (aka partition) adsorption isotherms were obtained for the aqueous CI Disperse Red 15/PET fibre system which took the generic form of line I in Figure 1. These findings were subsequently confirmed by other workers for the disperse dye/PET fibre system 19,[22][23][24] as well as for the adsorption of disperse dyes on other types of fibre (e.g., PA, 22,25,26 PP, 27 CA 8,19,[28][29][30] PAN, 31,32 CV, 33 CTA 30 and wool 34 ; see Burkinshaw 5 for a summary).…”
Section: Thermodynamic Analysis Of the Aqueous Disperse Dye Adsorptio...supporting
confidence: 72%
See 1 more Smart Citation
“…From the perspective of the disperse dye/PET fibre system, in 1954, Schuler and Remington 18 observed that rectilinear, Nernst (aka partition) adsorption isotherms were obtained for the aqueous CI Disperse Red 15/PET fibre system which took the generic form of line I in Figure 1. These findings were subsequently confirmed by other workers for the disperse dye/PET fibre system 19,[22][23][24] as well as for the adsorption of disperse dyes on other types of fibre (e.g., PA, 22,25,26 PP, 27 CA 8,19,[28][29][30] PAN, 31,32 CV, 33 CTA 30 and wool 34 ; see Burkinshaw 5 for a summary).…”
Section: Thermodynamic Analysis Of the Aqueous Disperse Dye Adsorptio...supporting
confidence: 72%
“…The fundamental thermodynamic aspects of the aqueous disperse dye adsorption process were established primarily using the disperse dye/CA fibre system (e.g., see Bird et al [7][8][9][10][11][12][13][14][15][16][17] ) and the disperse dye/PET fibre system (e.g., Schuler and Remington 18 and Remington and Schroeder 19 ) in the 1950s/1960s (see Burkinshaw 5,20 and Peters 21 and the references therein for detailed accounts of this large area).…”
Section: Thermodynamic Analysis Of the Aqueous Disperse Dye Adsorptio...mentioning
confidence: 99%
“…In the 1950s, support for Clavel and Stanisz' hypothesis was provided by findings (eg, [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ) that disperse dye solubility is promoted by both increasing temperature and commercial dispersing agents. Indeed, Clavel and Stanisz' aqueous solution theory is nowadays widely believed to offer a reasonable explanation of the likely events that occur during an aqueous disperse dyeing process for PET fibres.…”
Section: Conventional Models Of the Mechanism Of Disperse Dye Adsorptionmentioning
confidence: 99%
“…Investigations have been carried out in this field in relation to the particle size of the dye dispersion [ 19,23,31 ]; crystallographic forms of the dye [ 1,27,28]; solubility of dye in water [2,8]; polarity of the dye molecules [26]; and chemical constitution of the dye molecules [10,25,30]; size and shape of dye molecules [11,12,14]; concentration of dye in the dyebath [20]; nature and concentration of dispersing agent [3,6]; dyeing temperature [4,13,24]; nature of the fiber, crystallinity, and orientation of fiber matrix [7,9,17,21,22,32]; all these indicate that many factors influence dyeing of disperse dyes on synthetic fibers.…”
Section: Introductionmentioning
confidence: 99%